\(a,127-\left(y-15\right)=86\)
\(y-15=127-86\)
\(y-15=41\)
\(y=41+15\)
\(y=56\)
\(b,2\times\left(y-12\right)+18=164\)
\(2\times\left(y-12\right)=164-18\)
\(2\times\left(y-12\right)=146\)
\(y-12=146:2\)
\(y-12=73\)
\(y=73+12\)
\(y=85\)
Học tốt
a) 127 - (y - 15) = 86
y - 15 = 127 - 86
y - 15 = 41
y = 41 + 15
y = 56
Vậy y = 56.
b) 2 (y - 12) + 18 = 164
2 (y - 12) = 164 - 18
2 (y - 12) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
Vậy y = 85.
127 - ( y - 15 ) = 86
y - 15 = 127 - 86
y - 15 = 41
y = 41 + 15
y = 56
2 x ( y - 12 ) + 18 = 164
2 x ( y - 12 ) = 164 - 18
2 x ( y - 12 ) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
127-(y-15)=86
(y-15)=127-86
(y-15)=41
y=41+15
y=56
vậy x=56
2×(y-12)+18=164
2×(y-12)=164-18
2×(y-12)=146
(y-12)=146:2
(y-12)=73
y=73+12
y=85
vậy y=85
a, 127 - ( y - 15 ) = 86
y - 15 = 41
y = 56
b, 2 x ( y - 12 ) + 18 = 164
2 x ( y - 12 ) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
Trả lời:
a) \(127-\left(y-15\right)=86\)
\(\Leftrightarrow y-15=41\)
\(\Leftrightarrow y=56\)
Vậy \(y=56\)
b) \(2\times\left(y-12\right)+18=164\)
\(\Leftrightarrow2\times\left(y-12\right)=146\)
\(\Leftrightarrow y-12=73\)
\(\Leftrightarrow y=85\)
Vậy \(y=85\)